1995
DOI: 10.1161/01.res.76.6.958
|View full text |Cite
|
Sign up to set email alerts
|

Low Concentration of Oxidized Low-Density Lipoprotein and Lysophosphatidylcholine Upregulate Constitutive Nitric Oxide Synthase mRNA Expression in Bovine Aortic Endothelial Cells

Abstract: Endothelium-dependent relaxation is markedly reduced in atherosclerotic arteries. Recently, the endothelium-dependent relaxing factor has been identified as nitric oxide (NO). We used RNase protection assay and immunoblotting to elucidate the effect of atherogenic lipoprotein on the expression of constitutive NO synthase (cNOS) mRNA and protein levels in bovine aortic endothelial cells. Twenty-four-hour exposure to a low concentration of oxidized low-density lipoprotein (10 micrograms protein/mL) upregulated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
1
4

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(86 citation statements)
references
References 35 publications
3
78
1
4
Order By: Relevance
“…On the other hand, LysoPC can also play an important antiatherogenic role by, in part, increasing the local synthesis of nitric oxide in the initial phases of the formation of atherosclerotic plaques, leading to vasodilation [44,45]. The antiatherogenic properties of LysoPC may also include its capacity to regulate macrophage-derived cholesterol homeostasis [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, LysoPC can also play an important antiatherogenic role by, in part, increasing the local synthesis of nitric oxide in the initial phases of the formation of atherosclerotic plaques, leading to vasodilation [44,45]. The antiatherogenic properties of LysoPC may also include its capacity to regulate macrophage-derived cholesterol homeostasis [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…This effect is similar to the described response for lysoPC in other cultured endothelial cells. The role of lysoPC in the increased synthesis of e-NOS has been clarified in human umbilical vein endothelial cells and bovine arterial endothelial cells (18,19). Treatment of endothelial cells with lysoPC resulted in an increased transcription of the e-NOS mRNA in these cells, followed by an increased amount of protein and the corresponding activity.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the lysoPC content of atherosclerotic arteries is higher than in normal vessels, and oxidized low-density lipoprotein displays a great proportion of lysoPC (17). LysoPC is able to increase the production of NO by endothelial cells by enhancing endothelial NO synthase (e-NOS) transcription (18,19), besides acting as an inhibitor of platelet aggregation (20). This evidence shows that lysoPC is potentially pro-atherogenic by inducing the production of several growth factors and the expression of chemoattractant genes (21).…”
mentioning
confidence: 99%
“…Evidence indicates that the increase in caveolin regulation in cells exposed to high levels of LDL-cholesterol results directly from an increase in the transcription of the eNOS gene induced by the higher cellular content of cholesterol 30 . In vitro studies have shown that, when endothelial cells are exposed to low concentrations of oxidized LDL (LDL-ox) for more than 24 hours, an increase in eNOS mRNA is observed, but in high concentrations of LDL-ox, this effect is reversed 31,32 . These observations show the existence of a correlation between the production of nitric oxide, hypercholesterolemia, and lipid peroxidation.…”
Section: Total Oxysterolsmentioning
confidence: 99%